Kalunga sociobiodiversity from the perspective of undergraduate students at the University of Brasília - UnB - Noara Modesto Pimentel; Monica Castagna Molina (Revista Brasileira de Educação do Campo)
This article presents a bibliographical review of UnB course completion works that addressed the Kalunga Territory, mainly students graduating from the Degree in Rural Education (LEdoC), between the years 2013 and 2020, on the socio-biodiversity of the Kalunga Territory. The methodological procedures used consisted of the analysis of 17 course completion works on the Kalunga Territory; search for the scientific names and uses of wood cataloged by Cunha (2015); review of non-timber uses and field notes collected in the post-doctoral stage. It was identified that among the 17 final course works on the Kalunga Historical Site, 03 of them were produced by the courses: Geography; Linguistics; and Energy Engineering. Of this total of studies, 14 were prepared by LEdoC graduates; 11 of these works are by quilombolas who reside in the territory; 03 are from students who graduated from LEdoC and are not quilombolas. Among the 36 trees listed with their respective popular names, 22 of them showed a correspondence between the popular name and the scientific name presented in the literature consulted, therefore, 07 species did not have their scientific names indicated. It is noteworthy that another 7 species were matched only in one of the field guides.